1988
DOI: 10.1021/jo00244a036
|View full text |Cite
|
Sign up to set email alerts
|

Regioselectivity of electrophilic aromatic substitution: syntheses of 6- and 7-sulfamoylindolines and -indoles

Abstract: The previously reported chlorosulfonation of l-acetyl-5-bromoindoline at the 7-position is in error. In actuality, the 6-substituted product is the sole regioisomer produced. This regiochemical assignment is based on NMR data and confirmed by X-ray analysis. We have prepared the first 7-sulfamoylindoline and the corresponding indole from indoline using the indoline nitrogen to direct sulfamoylation intramolecularly to the 7-position. The new 7-substituted derivatives may prove to be important as intermediates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Although the indoline sulfonamide hit structures were listed by the supplier as the corresponding indoline-7-sulfonamides, it was concluded that the compounds must be 6-sulfonamides (as illustrated in Figure 2 ), as there were no general methods in the literature to prepare the 7-sulfonamide hits. Specifically, electrophilic aromatic chlorosulfonylation of 5-bromo- N -acetyl-indoline affords the product of electrophilic aromatic substitution at the sterically preferred 6-position rather than the presumed 7-position, as clearly and definitively demonstrated by Borror [ 29 ]. Yet, widespread errors persist in the literature regarding the regiospecificity of sulfonylation of indolines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the indoline sulfonamide hit structures were listed by the supplier as the corresponding indoline-7-sulfonamides, it was concluded that the compounds must be 6-sulfonamides (as illustrated in Figure 2 ), as there were no general methods in the literature to prepare the 7-sulfonamide hits. Specifically, electrophilic aromatic chlorosulfonylation of 5-bromo- N -acetyl-indoline affords the product of electrophilic aromatic substitution at the sterically preferred 6-position rather than the presumed 7-position, as clearly and definitively demonstrated by Borror [ 29 ]. Yet, widespread errors persist in the literature regarding the regiospecificity of sulfonylation of indolines.…”
Section: Resultsmentioning
confidence: 99%
“…Bromination of the N -acetyl indoline at the 5-position was performed by exposure of N -acetylindoline 6 to N -bromosuccinimide [ 29 , 30 ] in the presence of a catalytic amount of ammonium acetate to afford 7a in an 83% yield ( Scheme 1 ). Chlorination with N -chlorosuccinimide was more sluggish and provided the 5-chloroindoline derivative Figure S1 7b [ 31 ] in variable yield and required a tedious chromatographic purification.…”
Section: Resultsmentioning
confidence: 99%
“…HRMS (ESI) spectra were recorded with a Thermo Finnigan MAT 95XL mass spectrometer. The preparation and characterization of compounds 1a ,10 3a – 8a ,10 3b 19 were carried out as reported previously.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, we attempted to incorporate an indoline motif into the cycloaddition precursor. The precursor ( 15 ) was prepared in 5 steps by following known literature procedures 11. Using the present reaction conditions, the precursor ( 15 ) was converted into the corresponding indoline‐fused 1,2,3‐triazolobenzothiadiazepine 1,1‐oxide ( 16 ) in moderate yield (Scheme ).…”
Section: Methodsmentioning
confidence: 99%